Postpartum consultation: Occurrence, requirements and expectations - Carlgren Ingrid; Berg Marie (BMC, 2008)
Abstract Background As a matter of routine, midwives in Sweden have spoken with women about their experiences of labour in a so-called 'postpartum consultation'. However, the possibility of offering women this kind of consultation today is reduced due to shortage of both time and resources. The aim of this study was to explore the occurrence, women's requirements of, and experiences of a postpartum consultation, and to identify expectations from women who wanted but did not have a consultation with the midwife assisting during labour. Methods All Swedish speaking women who gave birth to a live born child at a University Hospital in western Sweden were consecutively included for a phone interview over a three-week period. An additional phone interview was conducted with the women who did not have a postpartum consultation, but who wanted to talk with the midwife assisting during labour. Data from the interviews were analysed using qualitative content analysis. Results Of the 150 interviewed women, 56% (n = 84) had a postpartum consultation of which 61.9% (n = 52) had this with the midwife assisting during labour. Twenty of the 28 women who did not have a consultation with anyone still desired to talk with the midwife assisting during labour. Of these, 19 were interviewed. The content the women wanted to talk about was summarized in four categories: to understand the course of events during labour; to put into words, feelings about undignified management; to describe own behaviour and feelings, and to describe own fear. Conclusion The survey shows that the frequency of postpartum consultation is decreasing, that the majority of women who give birth today still require it, but only about half of them receive it. It is crucial to develop a plan for these consultations that meets both the women's needs and the organization within current maternity care.